Formalization is just the beginning: Analyzing post-formalization successes and challenges in Peru's small-scale gold mining sector. (December 2021) - Martinez, Gerardo; Smith, Nicole M.; Malone, Aaron
Abstract: In recent years, the formalization of artisanal and small-scale gold mining (ASGM) activities has become a key strategy for governments to better govern and regulate the sector. While scholars have focused on examining the viability of formalization itself, little is known about the outcomes once ASGM operations become formal, or whether formalization efforts are sustainable. Peru has made great strides on simplifying the formalization process and has formalized over 9600 artisanal miners. Drawing on a case study from one of these formalized operations, this research examines postformalization outcomes. Findings from interviews with government officials and members of the ASGM community in one of the most important ASGM regions of Peru, Puno, demonstrate that formalization has yielded mixed results. Formal ASGM operations have improved health and safety practices and labor conditions, and miners believe their environmental awareness has increased. Despite these changes, miners who have become formalized feel even more pursued and scrutinized than they did when they operated informally, and they continue to face challenges obtaining technical support and accessing capital. We argue that although some progress has been made in formalization efforts, the problems and weaknesses within the approach may inadvertently push miners back into informality.We conclude that in order for formalization to be more fruitful for governments and miners, governments working on formalizing ASGM activities would greatly benefit from the creation of a solid postformalization strategy focused on educating and supporting formal ASGM operations. Highlights: Analyzes the benefits and challenges of formalization from the perspectives of government officials and miners. Formal ASGM operations have made changes in health and safety protocols, labor organization, and environmental protection. Post-formalization requirements can lead miners to revert to informality if support is not provided. Provides insights for governments and international organizations as they tailor policies, regulations, and donor projects. Concludes that governments would benefit from the creation of a post-formalization strategy to support formal miners.